Diverse Presentation of Breath Holding Spells: Two Case Reports with Literature Review - Geetanjali Rathore; Paul Larsen; Cristina Fernandez; Manish Parakh (Case Reports in Neurological Medicine)
Breath holding spells are a common and dramatic form of syncope and anoxic seizure in infancy. They are usually triggered by an emotional stimuli or minor trauma. Based on the color change, they are classified into 3 types, cyanotic, pallid, and mixed. Pallid breath holding spells result from exaggerated, vagally-mediated cardiac inhibition, whereas the more common, cyanotic breathholding spells are of more complex pathogenesis which is not completely understood. A detailed and accurate history is the mainstay of diagnosis. An EKG should be strongly considered to rule out long QT syndrome. Spontaneous resolution of breath-holding spells is usually seen, without any adverse developmental and intellectual sequelae. Rare cases of status epilepticus, prolonged asystole, and sudden death have been reported. Reassurance and education is the mainstay of therapy. Occasionally, pharmacologic intervention with iron, piracetam; atropine may be of benefit. Here we present 2 cases, one of each, pallid and cyanotic breath holding spells.